Combined Analytical Py-GC-MS, SEM, FTIR and C-13 NMR for Investigating the Removal of Trace Metals from Aqueous Solutions by Biochar - Andrade, Mineia A. M. de [UNESP]; Monteiro, Adnivia S. C.; Gontijo, Erik S. J. [UNESP]; Bueno, Carolina C. [UNESP]; Macedo, Joao C. A. [UNESP]; Rangel, Elidiane C. [UNESP]; Melo, Darllene S. [UNESP]; Montero, Jose I. Z. [UNESP]; Rosa, Andre H. [UNESP] (Soc Brasileira Quimica, 2020)
In this study, the efficiency of biochar (BC) produced from sugarcane bagasse at different pyrolysis temperatures (300, 400, 500 and 600 degrees C) for simultaneous removal of Cd-II, Pb-II, Cu-II, Cr-III, Ni-II and Zn-II ions from aqueous solutions was assessed. All BC were characterized using scanning electron microscopy (SEM), Fourier transform infrared (FTIR). C-13 nuclear magnetic resonance (C-13 NMR) and pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS). The effects of pyrolysis temperature, initial adsorbate concentration and adsorbent dosage on adorption capacity of BC were examined through batch experiments. The BC efficiency was also evaluated after a desorption cycle. The maximal adsorptions (C-II: 51.50%. Crm: 74.35%. Cu-III: 91.18%, Ni-II: 47.05%. Pb-II: 96.17% and Zn-II: 40.50%) were observed for BC produced at 500 degrees C, probably because of its higher porosity and presence of functional groups detected by SEM and FTIR. The maximum adsorption capacity for Cd-II, Cr-III, Cu-II, Ni-II and Zn-II (ions fitted to Langmuir model) were 175, 303, 455. 156 and 128 mu g g(-1). respectively. The predominance of phenolic groups observed in Py-GC-MS data may explain the high percentage of multi-element removal. Experimental data were best fitted to pseudo-second order, Sips and Freundlich models. The BC presented good removal results after a desorption cycle.
Keywords: low-cost adsorbents; adsorption; heavy metals; multi-element solution; isotherms